The role of students’ leadership in environmental conservation at higher education institutions - Mohamed, Mohamed Jama; Omar, Abukar Mukhtar; Jama, Liban Abdullahi (Frontiers in Education, 2025)
This study addressed the critical issue of how student leadership impacts environmental conservation in higher education institutions (HEIs), despite the growing environment-related problems this topic remains underexplored. The primary focus of this study was to investigate contribution of student organizations, leadership training programs, and collaboration partnerships with external organizations toward fostering environmental conservation among students. The study used a quantitative research design, data was collected through structured questionnaire from 331 students, and SEM-PLS was used to analyze the collected data. The findings revealed a significant and positive correlation between student organizations, leadership training programs, and collaboration partnerships with external organizations and environmental conservation. These findings highlight the important role played by HEIs in fostering environmental conservation through student leadership development programs. These findings underscore the need for HEIs to integrate student leadership into institutional strategies to build environmental competencies and promote environmental protection. The study contributes to the existing literature by placing student leadership as a strategic pathway toward sustainability in higher education.